SPORT ACTIVITY, EDUCATION AND ITS CHARACTERISTICS - Abduazimov Sabirjon Utkurovich (Proximus Journal Publishing, 2024)
The role and importance of physical education and sports in the formation of the young generation is studied in the article. Education and its features are discussed in sports activities.
Keywords: Physical culture; physical education and sports; adult generation